Introducing ArcGIS API 4 for JavaScript : turn awesome maps into awesome apps - Rubalcava, Rene (Apress, 2017)
Learn to use the ArcGIS API 4 for JavaScript to build custom web mapping applications. This book teaches you to easily create interactive displays of geographic information that you can use to tell stories and answer questions. Version 4 of the ArcGIS API for JavaScript introduces new patterns and fundamental concepts, including 3D mapping capabilities. You will learn the fundamentals of using the API in order to get the most out of it. Covering key concepts and how different components work together, you will also learn how to take advantage of the Widget framework built into the API to build your own reusable widgets for your own ArcGIS JSAPI applications. Including a series of samples you can use to leverage the API for your own applications, Introducing ArcGIS API 4 for JavaScript helps you take your existing knowledge of JavaScript to a new level, and add new features to your app libraries. What You'll Learn Create both 2D and 3D custom web mapping applications Work with popups and custom widgets Leverage the ArcGIS platform in your applications Utilize custom visualizations Who This Book Is ForDevelopers who need to learn the ArcGIS JSAPI for work or school. Those with some JavaScript experience; GIS or mapping experience is not required.